Implementasi Lembar Kerja Peserta Didik Interaktif Berbasis Hots Tema 7 Subtema 1 Di Kelas 1 SD - Mesi Pradrya Br Silalahi; Faizal Faizal (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2022)
Interactive LKPD is LKPD that is active and creates mutual action and can collaborate with several learning media that are able to provide direct learning experiences to students so that they are encouraged to always be active in learning. The aim of the research is to describe the development procedures, level of validity, and level of practicality of the product being developed. The development model used is ADDIE with 5 stages, namely: Analyze, Design, Develop, Implement and Evaluate. The implementation results obtained in the research show that the level of validity of the material on the product is 96.6% and is in the very valid category, the level of validity of learning on the product is 100% and is in the very valid category and the level of language validity on the product is 97.8 % and is in the very valid category. The level of product practicality obtained from teacher responses was 93.3% and was in the very practical category. Based on the results of the implementation of the research, it can be concluded that the HOTS-based Interactive Student Worksheet as a whole can be used in learning..